1996
DOI: 10.1038/bjc.1996.237
|View full text |Cite
|
Sign up to set email alerts
|

Identification of leukaemic cells in bone marrow and blood samples by a new cytofluorometric assay

Abstract: Summary The expression of thymidine kinase -an enzyme of the DNA precursor pathway -is strictly regulated during the normal cellular cycle, but is much higher and permanently expressed in malignant growing cells. We used this fact to detect neoplastic cells in samples freshly taken from leukaemia patients and kept frozen in liquid nitrogen until analysis. Using a new cytofluorometric assay for thymidine kinase in single cells, we were able to identify leukaemic cells in a surplus of normal ones. Our results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…(1) It has been demonstrated that circulating cells of fetal origin include trophoblasts, fetal lymphocytes, nucleated red blood cells and hematopoetic stem cells [3]. We showed that trophoblasts and fetal cord blood cells express high intracellular levels of TK activity, whereas normal adult peripheral blood is totally TK-negative (this study and [17]). (2) The small cell population with high TK activity specifically occurs in peripheral blood samples of pregnant women and not in the circulation of non-pregnant individuals.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…(1) It has been demonstrated that circulating cells of fetal origin include trophoblasts, fetal lymphocytes, nucleated red blood cells and hematopoetic stem cells [3]. We showed that trophoblasts and fetal cord blood cells express high intracellular levels of TK activity, whereas normal adult peripheral blood is totally TK-negative (this study and [17]). (2) The small cell population with high TK activity specifically occurs in peripheral blood samples of pregnant women and not in the circulation of non-pregnant individuals.…”
Section: Discussionmentioning
confidence: 51%
“…Analysing peripheral blood cells (about 30 million per individual) of 24 non-pregnant women (without any previous pregnancy) and 13 male individuals, we could not detect TK-positive cells (Fig. 2, see also [17]). Strikingly, using the same approach to analyse 14 pregnant women we observed a very small cell population with high TK activity (Fig.…”
Section: Patientmentioning
confidence: 91%
See 1 more Smart Citation